Fragile : Terres d'empathie = Fields of Empathy. - Hegyi, Lóránd; Viola, Eugenio; Exhibition. Fragile : Terres d'empathie = Fields of Empathy. Saint-Étienne. Musée d'Art Moderne de Saint-Etienne Métropole. 2009-05-16. 2009-08-16 (Saint-Etienne : Musée d'Art Moderne de Saint-Etienne Métropole, 2009)
Barabash, Ruth ; Bartolini, Massimo ; Boggash, Frauke ; Bolla, Marina ; Bournigault, Rebecca ; Bresson, Yves ; Cantoni, Davide ; Cattaneo, Alice ; Cecchini, Loris ; Choi, Dae-Jin ; Uyl, Tessa Manon den ; Fauchard, Karin ; Flexner, Roland ; Fogli, Andrea ; Garaicoa, Carlos ; Gennari, Francesco ; Giletta, Ugo ; Grassino, Paolo ; Gray, Kevin Francis ; Han, Myung-Ok ; Hapaska, Siobhán ; Kimsooja ; Koller, Bernd ; Kopp, Jan ; Kwon, In-Sook ; Lehocká, Denisa ; Manigaud, Eric ; Manto, Dacia ; Mattii, Maria Carla ; Mezzaqui, Sabrina ; Mirra, Helen ; Moro, Liliana ; Muniz, Vik ; Namazi, Sirous ; Nolan, Isabel ; Paris, Marina ; Pepperstein, Pavel ; Perez Simao, Marina ; Pétrovitch, Françoise ; Revesz, Laszlo Laszlo ; Rubiku, Anila ; Sawa, Hiraki ; Seiz, Fabian ; Sena, Francesco ; Szil, Katalin ; Takemura, Kei ; Tarkawian, Mariusz ; Toguo, Barthélémy ; Wallach, Paul ; Weinberger, Lois ; Sookyung Yee
biog. ind. tent., gr. tent. p. 145-155
boek
Keywords: Saint-Etienne